PENINGKATAN KAPASITAS KELOMPOK SADAR WISATA (POKDARWIS) DALAM PENGELOLAAN DAYA TARIK EKOWISATA PULAU POMBO KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Latupapua, Yosevita; Siahaya, Troice; Latupapua, Lesly (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2025)
TWA Pulau Pombo, designated as an ecotourism area, attracts numerous visitors due to its diverse natural and cultural attractions. However, the role of the local Tourism Awareness Group (Pokdarwis) has not been fully optimized. This community service program (PKM) aims to enhance the understanding of Pokdarwis members regarding the 3A components (Attraction, Amenity, Accessibility), Sapta Pesona, and tourism awareness. The program was implemented through a socialization approach using lectures and group discussions, accompanied by evaluation through pre-test and post-test methods. A total of 15 participants from the Pokdarwis of Tulehu Village took part in the activities and showed high enthusiasm during the sessions. The evaluation was conducted to measure participants’ level of understanding before and after the program. The results indicated a significant improvement in participants’ comprehension, as reflected in the increased post-test scores. Overall, the socialization program served as an essential platform to strengthen community understanding of tourism concepts, thereby fostering motivation and responsible participation in the sustainable development of TWA Pulau Pombo.